Enquete sur les ressources genetiques bovines de Cote d'Ivoire et mise au point d'un systeme de controle du troupeau - Poivey, J.P.; Seitz, J.L. (1977)
Survey report on the genetic stock at Bouake research station. Performances, genetic resources and herd control system are examined. Discussions on geographic distribution of N'Dama, Baoule and zebu breeds; trypanosomiasis control and socio-economic study of the environment included.